Employee Performance: Career Development, Motivation, and Workplace Environment Impact : Peningkatan Kinerja Karyawan: Dampak Pengembangan Karier, Motivasi, dan Lingkungan Kerja - Yodik Lestyo Widi; Kumara Adji Kusuma (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the influence of career development, motivation, and workplace environment on employee performance within an organizational context. Employing a quantitative methodology with a sample size of 128 respondents selected through simple random sampling, the research confirmed significant positive effects of career development, motivation, and workplace environment on employee performance, individually and collectively. The findings support the acceptance of hypotheses indicating that career development, motivation, and workplace environment significantly influence employee performance. The results underscore the importance of holistic approaches in human resource management, emphasizing the need for organizations to invest in employee career growth, foster motivation, and create conducive work environments, thereby enhancing overall workforce productivity and efficiency.Highlights : Comprehensive Influence: Career development, motivation, and workplace environment collectively shape employee performance, emphasizing the interconnectedness of these factors in organizational settings. Significant Positive Effects: The study confirms the positive impact of career development, motivation, and a conducive workplace on employee performance, underlining their essential role in enhancing workforce productivity. Strategic HR Emphasis: The research highlights the strategic importance of investing in employee career growth, motivation, and creating supportive work environments, providing valuable insights for effective human resource management practices. Keywords:Employee Performance, Career Development, Motivation, Workplace Environment, Human Resource Management